A broader view on brands' growth and decline. (March 2020) - Formisano, Marcello; Pauwels, Koen; Zarantonello, Lia
What does it take to grow a brand? How to avoid its decline? Some popular answers to these questions can be found in the research by Byron Sharp and others from the Ehrenberg-Bass (EB) Institute on "how brands grow." In this article, we propose that such an approach, despite its strengths, lends itself to some limitations when taken too literally. We maintain that a broader notion and role of branding—encompassing brand equity, brand portfolio, and circular relationship of attitudes and behaviors—should be adopted by marketeers to derive better managerial implications for sustainable brand growth. We, therefore, invite marketers to not oversimplify Dirichlet evidences by thinking of availability as the only (costly) response to all marketing challenges.